Asas Legalitas dan Lex Temporis Delicti Dalam Reformasi KUHP Indonesia: Legalitas and Lex Temporis Delicti In Indonesia’s Criminal Code Reform - Aisyah Nurhalizah; Bayu Wishnu Buana (Universitas Semarang, 2025)
This study critically examines the existence and implementation of the principles of legality and lex temporis delicti within Indonesia’s criminal law codification policy through a comparative analysis of the old Criminal Code (KUHP), the new KUHP, and the criminal law systems of the Continental and Anglo-Saxon traditions. The urgency of this research arises from the fundamental shift in Indonesia’s penal paradigm following the enactment of the new KUHP, particularly the expanded interpretation of legality through the recognition of living law and the adoption of the lex mitior principle as a progressive exception to lex temporis delicti. Employing a normative legal methodology with statutory and comparative approaches, this study analyzes primary and secondary legal materials to assess the doctrinal coherence and policy implications of these developments. The findings demonstrate that the new KUHP marks a departure from classical legalism toward a more adaptive and socially responsive framework oriented toward human rights protection. The legality principle is recontextualized through the broadening of legitimate legal sources, while lex temporis delicti is recalibrated to accommodate substantive justice by integrating lex mitior. The novelty of this study lies in its integrative analysis that combines normative, comparative, and codification-policy perspectives, revealing Indonesia’s current transition toward a more humanistic, contextual, and internationally aligned model of criminal law. Penelitian ini menganalisis secara kritis eksistensi dan penerapan asas legalitas serta lex temporis delicti dalam politik kodifikasi hukum pidana Indonesia melalui kajian komparatif terhadap KUHP lama, KUHP baru, dan sistem hukum pidana tradisi kontinental serta Anglo-Saxon. Urgensi penelitian ini muncul dari perubahan paradigma pemidanaan yang mendasar setelah disahkannya KUHP baru, khususnya terkait perluasan makna asas legalitas melalui pengakuan living law dan penerapan prinsip lex mitior sebagai pengecualian progresif terhadap lex temporis delicti. Dengan menggunakan metode penelitian hukum normatif melalui pendekatan perundang-undangan dan perbandingan hukum, penelitian ini menganalisis bahan hukum primer dan sekunder untuk menilai koherensi doktrinal serta implikasi kebijakan dari perkembangan tersebut. Temuan penelitian menunjukkan bahwa KUHP baru menandai pergeseran dari legalisme klasik menuju kerangka hukum pidana yang lebih adaptif dan responsif terhadap perkembangan sosial serta berorientasi pada perlindungan HAM. Asas legalitas direkontekstualisasikan melalui perluasan sumber hukum yang diakui, sedangkan lex temporis delicti dikalibrasi ulang untuk mengakomodasi keadilan substantif melalui integrasi lex mitior. Kebaruan penelitian ini terletak pada analisis integratif yang memadukan perspektif normatif, komparatif, dan politik kodifikasi, yang mengungkap bahwa sistem hukum pidana Indonesia sedang berada dalam masa transisi menuju model yang lebih humanistik, kontekstual, dan selaras dengan standar hukum internasional.